2002
DOI: 10.1108/09540910210444692
|View full text |Cite
|
Sign up to set email alerts
|

Reactions between Sn–Ag–Cu lead‐free solders and the Au/Ni surface finish in advanced electronic packages

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
71
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 11 publications
3
71
0
Order By: Relevance
“…It is interesting to note that the quaternary (Cu 1-p-q Au q Ni p ) 6 Sn 5 IMC was well adhered to the Ni when the solder contained 0.75 wt.% Cu but was detached from the Ni when the solder contained 0.5 wt.% Cu. Laurila et al 19 obtained results that were consistent with those of Ho et al 5 and Shiau et al 18 Both Stepniak 20,21 and Zhang et al 17 found that the addition of Au increased the degradation rate of a standard multilayer thin-film UBM composed of Al, Ni(V), and Cu (Al/Ni(V)/Cu). In fact Stepniak reported that the addition of Au counteracts the reduction in the Ni-solder reaction rate that V-doping is know to provide in an Au-free environment.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…It is interesting to note that the quaternary (Cu 1-p-q Au q Ni p ) 6 Sn 5 IMC was well adhered to the Ni when the solder contained 0.75 wt.% Cu but was detached from the Ni when the solder contained 0.5 wt.% Cu. Laurila et al 19 obtained results that were consistent with those of Ho et al 5 and Shiau et al 18 Both Stepniak 20,21 and Zhang et al 17 found that the addition of Au increased the degradation rate of a standard multilayer thin-film UBM composed of Al, Ni(V), and Cu (Al/Ni(V)/Cu). In fact Stepniak reported that the addition of Au counteracts the reduction in the Ni-solder reaction rate that V-doping is know to provide in an Au-free environment.…”
Section: Introductionsupporting
confidence: 73%
“…However, when the Pb-Sn solder was doped with 0.5 wt.% Cu, no ternary (Au 1-x Ni x )Sn 4 IMC particles were found in the solder but rather Au was incorporated in the form of a quaternary (Cu 1-p-q Au q Ni p ) 6 Sn 5 phase at the Ni-solder interface. Shiau et al 18 found binary Ni 3 Sn 4 IMC at the Ni solder-interface when Cu was not present in the Sn-Ag solder and quaternary (Cu 1-p-q Au q Ni p ) 6 Sn 5 IMC at the Ni-solder interface when 0.75 wt.% Cu was present in the Sn-Ag solder. For 0.5 wt.% Cu in Sn-Ag solder the solder-Ni interface was composed of a mixture of binary Ni 3 Sn 4 IMC and quaternary (Cu 1-p-q Au q Ni p ) 6 Sn 5 IMC.…”
Section: Introductionmentioning
confidence: 98%
“…8 This strong sensitivity is similar to the Cu concentration sensitivity in the reaction between SnAgCu solders and Ni substrates. [10][11][12][13][14] However, note that the above Zn concentration sensitivity was established in bulk reactions where the supply of Zn was large. In other words, the Zn concentration remained almost constant.…”
Section: Introductionmentioning
confidence: 94%
“…14 The driving force for the migration of AuSn 4 is for this compound to seek Ni so that this binary compound becomes a Ni-saturated (Au 1Àx Ni x )Sn 4 . 9 In the high-Sn system, such as pure tin, 14 or the eutectic SnAg, 11,12,[19][20][21][22] AuSn 4 seems to have a much lesser tendency to migrate back to the interface. It was even claimed that Au embrittlement was no longer a problem for high-Sn solders.…”
Section: Introductionmentioning
confidence: 99%